PASTORAL CARE FOR MARRIED COUPLES DURING CRISIS PERIODS USING EFFECTIVE CBT METHODS BY AARON BECK, THE VALUE-SEMANTIC ORIENTATION OF CLASSICAL BIBLICAL COUNSELING BY JAY ADAMS, AND LOGOTHERAPY BY VIKTOR FRANKL - Fakhrutdinova, Ekaterina (Global Prosperity, 2025)
Abstract. The article focuses on pastoral care for married couples during crisis periods, integrating effective cognitive behavioral therapy (CBT) methods, the value-semantic orientation of classical biblical counseling, and logotherapy. The aim of the study is to demonstrate how pastoral support helps couples overcome crises by strengthening spiritual connections, replacing destructive behavioral patterns with constructive ones, and restoring harmony in relationships through the creation and discovery of new meanings. The research employed general scientific research methods, including analysis, synthesis, comparison, and generalization. The findings indicate that pastoral care is a critical element in supporting married couples through crises, helping preserve the marital bond, which serves not only as the foundation of family life but also as a source of grace, elevating natural love to the level of supernatural love. In moments of crisis, it is crucial to support and deepen this connection, guiding couples to find new meaning in shared life, maintain faith, and resolve internal conflicts. Effective pastoral methods include CBT, which helps couples recognize and replace destructive thought patterns that often lead to conflicts with more realistic and constructive beliefs. This approach reduces anxiety, improves communication, and strengthens emotional connections between partners. Additionally, biblical counseling emphasizes spiritual growth, moral values, and relationship restoration through deepened faith, highlighting the importance of spiritual unity in marriage. Viktor Frankl’s logotherapy complements the latter approach by encouraging couples to find meaning even in the most challenging circumstances, emphasizing the spiritual dimension of shared life and the pursuit of deeper understanding. Together, these approaches form a comprehensive support system for families during crises, providing not only psychological stability but also spiritual renewal, as well as promoting long-term marital strength and personal growth for each partner. The practical significance of the study lies in the development of a comprehensive pastoral care methodology aimed at harmonizing family relationships during crisis periods.